Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1029/2009jd011767
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Saharan dust on radionuclide aerosol activity levels in Europe? The 21–22 February 2004 case study

Abstract: In February 2004, a spectacular dust event was observed in the south of France. Associated with huge particulate matter deposition, unusual 137Cs concentrations were found in samples. Using the transport model CHIMERE‐DUST, we first show that these dust aerosols came from North Africa. More precisely, the question is whether this sudden increase of measured 137Cs concentrations was due to a huge amount of dust over a large region (with an usual radionuclide content) or due to an import of more concentrated air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The CHIMERE chemistry‐transport model may be used for urban to regional air pollution (including anthropogenic and biogenic emissions [ Bessagnet et al ., ]), for analysis and forecast [ Menut and Bessagnet , ], and for long‐range transport [ Menut et al ., ]. In this study, the model is used with only the mineral dust emissions and transport.…”
Section: Real Case Studymentioning
confidence: 99%
“…The CHIMERE chemistry‐transport model may be used for urban to regional air pollution (including anthropogenic and biogenic emissions [ Bessagnet et al ., ]), for analysis and forecast [ Menut and Bessagnet , ], and for long‐range transport [ Menut et al ., ]. In this study, the model is used with only the mineral dust emissions and transport.…”
Section: Real Case Studymentioning
confidence: 99%
“…It was shown that the sum of all model uncertainties (emissions, transport, deposition) and of the spread of the forecasted meteorology induces a variability in surface concentrations still higher than the required precision for European air quality forecast. A sensitivity study was presented in Menut et al (2009b) and it was shown that a very small area in the Sahara (around the position of the former French nuclear tests site during the 60s) may explain the sporadic (but low) radionuclides concentrations measured sometimes in the South of France. Finally, the dust emissions are only calculated using a bottomup approach and future interesting developments could be to merge these calculations with satellite data to improve the calculated emitted dust flux (as in Huneeus et al, 2012 at the global scale).…”
mentioning
confidence: 99%
“…137 Cs contamination detected in France during a Saharan dust event was suspected to be the result of leakage from past nuclear test sites in French Saharan territory (Danesi et al, 2008). Igarashi et al (2005) pointed out that close-in fallout from atmospheric nuclear explosions should have been an insignificant source of surface contamination of 90 Sr and 137 Cs around the test sites, thus negligible in aeolian dust transport; and French researchers drew similar conclusions (Menut et al, 2009;Masson et al, 2010). Only 0.7 % of the Saharan dust was ascribed to the test area, accounting for only a small percentage of the atmospheric 137 Cs peak concentrations recorded in France during the transport event (Menut et al, 2009).…”
Section: Appendix a A1 No Direct Link To Past Nuclear Testsmentioning
confidence: 55%
“…Igarashi et al (2005) pointed out that close-in fallout from atmospheric nuclear explosions should have been an insignificant source of surface contamination of 90 Sr and 137 Cs around the test sites, thus negligible in aeolian dust transport; and French researchers drew similar conclusions (Menut et al, 2009;Masson et al, 2010). Only 0.7 % of the Saharan dust was ascribed to the test area, accounting for only a small percentage of the atmospheric 137 Cs peak concentrations recorded in France during the transport event (Menut et al, 2009). These results indicate that the Saharan dust episode might have a common background with the present Asian dust case -degradation of grassland where the surface serves as a reservoir for anthropogenic radionuclide fallout.…”
Section: Appendix a A1 No Direct Link To Past Nuclear Testsmentioning
confidence: 62%
See 1 more Smart Citation